2014
DOI: 10.1093/cvr/cvu105
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-derived follistatin-like 1 functions to reduce neointimal formation after vascular injury

Abstract: Our findings indicate that muscle-derived Fstl1 attenuates neointimal formation in response to arterial injury by suppressing SMC proliferation through an AMPK-dependent mechanism. Thus, the release of protein factors from muscle, such as Fstl1, may partly explain why the maintenance of muscle function can have a therapeutic effect on the cardiovascular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 48 publications
1
67
0
Order By: Relevance
“…Therefore, the ability of omentin to reduce ERK activation is dependent, at least in part, on activation of AMPK. Previous reports have shown that AMPK stimulators can suppress agonist-induced ERK phosphorylation in various cells, including VSMCs and cardiac myocytes (30,31). Collectively, these data suggest that AMPK-mediated suppression of ERK activation participates in the beneficial actions of omentin on vascular remodeling.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, the ability of omentin to reduce ERK activation is dependent, at least in part, on activation of AMPK. Previous reports have shown that AMPK stimulators can suppress agonist-induced ERK phosphorylation in various cells, including VSMCs and cardiac myocytes (30,31). Collectively, these data suggest that AMPK-mediated suppression of ERK activation participates in the beneficial actions of omentin on vascular remodeling.…”
Section: Discussionsupporting
confidence: 58%
“…[29][30][31] Accumulating evidence indicates that skeletal muscle produces various secretory factors, also known as myokines, which can directly act on neighboring and remote organs. [32][33][34] We have shown that ischemic insult in hindlimb leads to an increase in muscle and circulating levels of NDNF. 5 It has also been shown that NDNF is mainly expressed in endothelial cells of skeletal muscles and that NDNF secretion from cultured endothelial cells is enhanced in response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent to which skeletal muscle produced FSTL1 contributes to the beneficial effects of regular exercise performed shortly after myocardial infarction[40] has yet to be determined. Nonetheless it is clear from transgenic mouse models that muscle-derived FSTL1 can attenuate neointimal formation in response to arterial injury by suppressing SMC proliferation and can improve revascularization following hind-limb ischemia by promoting angiogenesis[41,42]. Thus, skeletal muscle-dependent release of FSTL1 could have multiple therapeutic effects on the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%